Translation...the bridge of knowledge | الترجمة.. جسرُ المعرفة - Al Faleh | الفالح, Bodour bint Abdulaziz | بدور بنت عبدالعزيز (2024)
Opinions, information and cultures come from different media. From newspapers, news bulletins, dialogue and analytical sessions, and it is certain that this knowledge is brought from various languages, and this requires strenuous efforts undertaken by professional translators capable of conveying this information with credibility, and these people, I believe, are the unknown soldiers; As they are behind conjuring and transmitting this information; They build bridges of knowledge through “translation”, which is defined as the process of transferring written, visual or audio content from the source language to the target language, but I prefer it to be defined creatively as the process through which we learn about global movement; Whether political, military, economic, psychological or scientific. | تُستسقى الآراء والمعلومات والثقافات من وسائل الإعلام المُختلفة؛ من صحفٍ ونشرات أخبارٍ وجلساتٍ حوارية وتحليلية، ومن المُتيقن أنّ تلك المعارف تُستجلب من مُختلفِ اللغات، وهذا يتطلبُ جهودًا مضنية يقومُ عليها مترجمون محترفونَ قادرون على نقلِ تلكم المعلومات بمصداقيةٍ، وهؤلاءِ بظنّي أنّهم الجند المجهولون؛ إذ هم وراء استحضار تلكم المعلومات ونقلها؛ يمدّون جسور المعرفة عبر "الترجمة" التي تُعرَّف بأنها عملية نقل المحتوى المكتوب أو المرئيّ أو المسموع من اللغة المصدر إلى اللغة الهدف، إلا أنني أُحبّذ أن تُعرَّف إبداعيًا بالعملية التي نَتعرفُ من خلالها على الحراكِ العالميّ؛ سواءٌ أكان سياسيًّا أم عسكريًّا أم اقتصاديًّا أم نفسيًا أم علميًا.